Relationships are Key: Family Life Educators' Use of Social Networking Sites. Issue 2 (2nd April 2020) - Clary, Pam Carlson; Markham, Melinda Stafford; Myers-Bowman, Karen S.
Abstract: This exploratory study examined the use of social networking sites (SNSs) by Certified Family Life Educators (CFLEs). Using a phenomenological approach, 19 CFLEs were interviewed. The participants emphasized that their goal to be seen as professional, both on and offline, guided their use of SNSs. They took safeguards to establish a professional 'brand' by monitoring their online behavior and developing guidelines for ethical digital practice. Professional relationships were found to be key to CFLEs. Attention to the ethical and professional use of SNSs to provide guidance for CFLEs is a necessary next step for the field in today's digital world.